THE GENUS TETRACTINELLA BITTNER, 1890: MORPHOLOGY, UNLTRASTRUCTURE, AND 3D RECONSTRUCTION (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2002)
The species Tetractinella trigonella (Schlotheim, 1820) and Tetractinella hexagonalis (Bittner, 1890) are described. The former has been studied on specimens from several localities of the Anisian of Southern Alps (Italy) and from the type-area of Tarnowitz (upper Silesia, Poland). The second has been analyzed on specimens from the Southern Alps. Taxonomic description and morphologic and biometrical analysis of external characters were followed by a morphologic analysis of internal structures using transverse serial sections. The ultrastructural analysis of internal characters provided new information about the structure of the ornamentation of T. trigonella (the presence of tabulae with costae) and new data about the poorly known T. hexagonalis. Finally, the internal characters of T. trigonella were re-examined using software for 3-D reconstruction from serial sections to complement the traditional method of study.